Stock prices and macroeconomic variables nexus in South Asian countries - Zakaria, Muhammad; Junyang, Xi (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper examines the interactions between stock prices, exchange rate, interest rate, inflation and income in Bangladesh, India, Pakistan and Sri Lanka using monthly data for the period 1997:07 to 2013:06. The motivation is to establish the causal and cointegrating relationship between stock prices and macroeconomic variables. The results indicate that cointegration holds between these variables in all countries. Temporal causality results are mixed, from unidirectional causality to bi-directional and even no causality between stock prices and macroeconomic variables. Causality results generally support the ‘portfolio approach’ that stock prices lead changes in exchange rate. However, the results of impulse response analysis, based on the structural VAR model, support the ‘traditional approach’ and suggest that it is exchange rate innovations that affect stock prices. Variance decomposition analysis also supports the findings of impulse response analysis
Argumenta Oeconomica, 2016, Nr 2 (37), s. 93-130
Keywords: stock prices; South Asia; SVAR